2022
DOI: 10.1186/s12883-022-02608-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic effects of treatment protocols for febrile convulsive status epilepticus in children

Abstract: Background Febrile status epilepticus is the most common form of status epilepticus in children. No previous reports compare the effectiveness of treatment strategies using fosphenytoin (fPHT) or phenobarbital (PB) and those using anesthetics as second-line anti-seizure medication for benzodiazepine-resistant convulsive status epilepticus (CSE). We aimed to examine the outcomes of various treatment strategies for febrile convulsive status epilepticus (FCSE) in a real-world setting while compari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In addition, 39% of previously normally developing patients will present with new deficits during follow‐up, with longer electroclinical RSE duration being a predictor 32 . Importantly, some data suggest that using a standardized treatment protocol may be associated with improved outcomes 33 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, 39% of previously normally developing patients will present with new deficits during follow‐up, with longer electroclinical RSE duration being a predictor 32 . Importantly, some data suggest that using a standardized treatment protocol may be associated with improved outcomes 33 …”
Section: Discussionmentioning
confidence: 99%
“…They found that the time from onset of status epilepticus to TTM induction correlated with the outcome at T1, whereas the time from onset of late seizures at T4 to TTM initiation did not correlate with the outcome. Tokumoto et al (2022) reported the hourly protocol orient management including TTM aiming to start treatment around 6 h after onset (T1) for febrile convulsive status epilepticus reduced neurological sequelae and cases finally diagnosed as AE even though the ratio who underwent TTM were not different. Hoshide et al (2020) conducted a historical cohort study involving the use of therapeutic hypothermia in children with identified late seizures and a diagnosis of AESD confirmed at T4.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the clinical course and final diagnosis can be modified by acute treatment. For example, early intervention for children with febrile status epilepticus may prevent progression to AE ( Tokumoto et al, 2022 ). Notably, interventional studies for AEs vary in terms of the timing of treatment initiation across studies, implying that the purpose of treatment and the implications of treatment efficacy depend not only on the disease condition, but also on the timing of treatment initiation.…”
Section: Introductionmentioning
confidence: 99%